Систематический указатель статей к "Известиям ТПИ" 1965-1977 гг. в 4 ч. - Смирных Т. Г. Тамара Григорьевна; Беляева Г. Н. Галина Николаевна; Быстрова Г. М. Галина Марьяновна; Сончик К. К. Константин Константинович (Томск, [Б. и.], 1980)
Сплошная пагинация.